2018
DOI: 10.1080/10298436.2018.1508843
|View full text |Cite
|
Sign up to set email alerts
|

Influence of clogging on the hydrologic performance of a double layer porous asphalt

Abstract: Nowadays, the increasing urbanisation and the effect of climate change in cities has been a constant concern. In particular, the floods cause a significant increase in surface runoff, mostly on roads and parking areas. As an alternative to asphalt pavements, usually used in these areas, permeable pavements have been developed with Porous Asphalt (PA). These pavements allow the infiltration of water from the surface to the ground due to the high void content of the PA, thus reducing the surface runoff and incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Finally, the fracture toughness, Klc, of the mixture was calculated as an average of the Klc,i values using Eq. (5).…”
Section: Semi-circular Bending Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the fracture toughness, Klc, of the mixture was calculated as an average of the Klc,i values using Eq. (5).…”
Section: Semi-circular Bending Testmentioning
confidence: 99%
“…The TLPA specimens were found to better resist clogging compared to OLPA specimens. Afonso et al, [5] investigated the hydrological performance of TLPA. Their results showed that the type of clogging cycles and materials significantly affects the infiltration capacity of TLPA.…”
Section: Introductionmentioning
confidence: 99%
“…Pervious concrete (PC) generally contains no or minimal fine aggregate; due to the low cement content, coarse aggregates can form a large number of interconnected pores [1], so rainwater can freely infiltrate into the PC pavement and reduce the problem of urban waterlogging [2]. With time, different types of clogging material will be transported to the interior of a PC pavement under the action of rainwater or natural settlement [3], which will eventually reduce the permeability of PC and seriously reduce the service life of the pervious pavement [4].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies show that the noise reduction performance of double porous asphalt pavement was improved with the decrease of aggregate size distribution of the top layer [31]. The double layer porous asphalt has a good hydrological performance, and it was able to reduce the surface runoff from a precipitation of 100 mm/h, and the sand and soil used did not significantly affect its infiltration capacity [32].…”
Section: Introductionmentioning
confidence: 99%